A264 HELMINTH-INFECTION MOBILIZES HOST AND MICROBIAL FACTORS THAT CO-OPERATE TO SUPPRESS CHEMICAL-INDUCED COLITIS IN MICE. (26th February 2020) - Shute, A J; Callejas Pina, B E; Jayme, T S; Wang, A; Buret, A; McKay, D M
Abstract: Background: Infection with helminth parasites suppresses inflammation in murine model systems; for example, IL-10 is important in Hymenolepis diminuta -inhibition of DNBS-induced colitis. Bacteria-derived products can have anti-inflammatory effects. Given that infection with H. diminuta, or other parasitic worms, results in perturbation of the gut microbiota, the present study tested a role for bacteria in helminth-suppression of colitis by assessing reciprocity between IL-10 and butyrate signaling in the amelioration of colitis. Aims: To determine if a functional relationship exists between IL-10 and butyrate in the inhibition of colitis observed following infection with the lumen-dwelling tapeworm, Hymenolepis diminuta . Methods: Colitis was induced in male BALB/c mice by intra-rectal dinitrobenzene sulphonic acid (DNBS) (3 mg/~22g mouse), with necropsy and assessment 3 days later. Mice received either infection with five H. diminuta cysticercoids by gavage or daily butyrate enemas or acetate in their drinking water. Immunostaining assessed IL-10R protein expression on formalin-fixed sections of colon. The murine IEC4.1 epithelial cell line and epithelial organoids were treated with butyrate and mRNA for the IL10Rα chain assessed, as was colonic tissue from mice. Results: Mice infected with H. diminuta or receiving butyrate enemas (n=8–12) were protected from DNBS-induced colitis as gauged by colon length, and macroscopic disease and histopathology scores. Addition of acetate to the drinking water resulted in a more modest anti-colitic effect. Suppression of colitis was accompanied by increased epithelial expression of IL-10 in butyrate- and H. diminuta -treated mice, with the later also showing upregulation of the IL-10R on lamina propria cells; an effect negated by co-treating the mice with broad spectrum antibiotics. In vitro analyses revealed increased IL10Rα mRNA in butyrate-treated epithelia (n=4). Conclusions: This study begins to tease apart the host (i.e. IL-10) and bacterial (i.e. butyrate) molecules that mediate H. diminuta -evoked suppression of colitis in a murine model. These proof-of-principle data suggest that knowledge of the individual patient (i.e. immunological basis of their disease and their microbiota) may be a critical determinant of the success or failure of helminth therapy. Funding Agencies: CAG, CCCNSERC